Teachers in training’s conceptions about rural education - Serruto, Verónica (2024)
The teacher is one of the main actors in the learning process and his or her belief system influences his or her pedagogical practice. The objective of this research is to identify the conceptions of a group of education students in a highland province of Peru about rural education, their role in it and the characteristics of the students. A qualitative study using a semi-structured interview is proposed. The results showed that the participants recognize the cultural value of rurality and the needs and rights of its inhabitants, however, they continue to relate them to poverty and less development, which can be translated into discourses that transmit a hopeless and disadvantaged vision. Stereotypical conceptions of rural students were also identified, which may influence the construction of teachers’ expectations and have an impact on their performance and students’ academic achievement. Finally, there is evidence of limited knowledge about rural schools and multigrade education, which may be one of the reasons why they consider multigrade education as a negative characteristic of rural schools.